Melacak Al-Qur’an Bahasa Arab dalam Pandangan Barat - Lu'luatul Fauziah; Syafiin Mansur (Jurnal Budi Pekerti Agama Islam, 2025)
The study of the Qur'an in the West has a long history. It began with the tradition of orientalism in the Middle Ages and has evolved into a modern academic approach that relies on philology, historical, and hermeneutical. In the West, the study of the Qur'an was initially dominated by apologetic and polemic reasons. However, since the 19th century, scientific approaches have begun to dominate thanks to the research of figures such as Theodor Nöldeke, Ignaz Goldziher, and John Wansbrough. After that, the focus of modern research turned to the linguistic analysis and structure of the Arabic language of the Qur'an. It includes the study of semantics (Toshihiko Izutsu), stylistic analysis, and comparative studies between pre-Islamic Arabic dialects and the language of the Qur'an. Western scholars have diverse views on the Qur'an in Arabic. Some question the structure, origin, and cohesiveness of the text, while others acknowledge its uniqueness, coherence, and rhetorical power. Despite epistemological differences, this article analyzes the history of Qur'an study in the West, identifies the main methods used to analyze the Qur'an in Arabic, and outlines the various critical perspectives and appreciation of Western scholars on the linguistic character of the Qur'an. The results of the analysis show that, from the polemic paradigm, the study of the Qur'an is increasingly moving towards a more interdisciplinary scientific approach.